Hubungan Jenis Sumber Air Minum dengan Kualitas Air Minum Rumah Tangga pada Titik Sarana dan Titik Konsumsi di Kota Bekasi - Faradhila Aushafiana Manaf; Al Asyary (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Safe drinking water is a basic human need and an essential determinant of public health. Ensuring drinking water meets physical, chemical, and biological standards remains a challenge in densely populated urban areas, including Bekasi City. As a buffer zone for the capital city with rapid industrial and residential growth, Bekasi faces the risk of water source pollution due to domestic and industrial activities. This study aims to analyze the relationship between the type of drinking water source and the quality of household drinking water at the point of access and point of use in Bekasi City. The study used a cross-sectional design based on secondary data from the SKAMRT 2024. A total of 512 households were analyzed using the Chi-square test to examine the relationship between the type of water facility and water quality based on biological (E. coli), physical (TDS), and chemical (pH) parameters. The results showed that the main water source at the POA was KPSPAM piped water (81.8%), while at the POU was dominated by refilled water (52.3%). Water quality at the POU was generally better than at the POA. Statistical tests showed a significant relationship in biological parameters (p<0.05) at both points and in chemical parameters (p<0.05) at the POA, while physical parameters were not significant (p>0.05). The quality of household drinking water in Bekasi City is influenced by the type of water facility in terms of biological and chemical aspects at the POA, while the physical aspects are relatively the same and meet health standards.